2015
DOI: 10.1158/0008-5472.can-14-2842
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin–ERK Signaling Uncouples Slug Gene Regulatory Function

Abstract: Epithelial-mesenchymal transition (EMT) in cells is a developmental process adopted during tumorigenesis that promotes metastatic capacity. In this study, we advance understanding of EMT control in cancer cells with the description of a novel vimentin-ERK axis that regulates the transcriptional activity of Slug (SNAI2). Vimentin, ERK, and Slug exhibited overlapping subcellular localization in clinical specimens of triple-negative breast carcinoma. RNAi-mediated ablation of these gene products inhibited cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
128
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 39 publications
10
128
0
1
Order By: Relevance
“…Recent data from our consortium have shown that vimentin is required to support ERK-mediated Slug phosphorylation and activation in a cancer-related model (12). With this model, we could show that vimentin-ERK-Slug interaction amplifies EMT onset via a positive-feedback loop between vimentin and the transcription factor Slug, which has an established role in skin development and the EMT-like processes of wound healing (13)(14)(15).…”
Section: Wounds Vimentin Reconstitution In Vimmentioning
confidence: 76%
“…Recent data from our consortium have shown that vimentin is required to support ERK-mediated Slug phosphorylation and activation in a cancer-related model (12). With this model, we could show that vimentin-ERK-Slug interaction amplifies EMT onset via a positive-feedback loop between vimentin and the transcription factor Slug, which has an established role in skin development and the EMT-like processes of wound healing (13)(14)(15).…”
Section: Wounds Vimentin Reconstitution In Vimmentioning
confidence: 76%
“…We demonstrated that FiVe1 fully inhibited VIM-dependent cellular motility in scratch assays. VIM knockdown in post-EMT cells has been demonstrated to reorganize cellular morphology and inhibit migratory capacity, underscoring the notion that targeting VIM can antagonize EMT-induced CSC traits (39).…”
Section: Discussionmentioning
confidence: 87%
“…The view that vimentin potentiates Jagged function is corroborated by the data showing that Jagged expression correlates with vimentin expression in several tissues and in cancer, in particular. Elevated expression of both vimentin and Jagged has been implicated in tumor progression (6,8,10,16,(73)(74)(75)(76). Furthermore, observations in vimentin knockout mice links vimentin to defects in wound healing, fibrosis, inflammation, epidermal aging, and epithelial mesenchymal transition in cancer (4,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas IFs provide cells with mechanical stability, there is mounting evidence indicating that IFs are involved in a range of metabolic, signaling, and regulatory processes that are unrelated to mechanical functions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The vimentin IF has been shown to act as a scaffold for signaling proteins that regulate epithelial mesenchymal transition (EMT), cancer cell invasion, wound healing and tissue repair, tissue aging, as well as inflammatory signaling (3,4,(6)(7)(8)10). Vimentin anchors and organizes adhesion molecules as well as actomyosin complexes (15) to regulate cell adhesion and migration (4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation